Does gender matters? understanding correctional staff occupational stress - Ku Ishak, Awanis; Razak, Hanissah A; Mohamad, Armanurah (2017)
Excessive occupational stress is an imperative issue in any organizations because it prohibits wellness that deters employees’ optimal performance. Correctional staff are among occupation most affected by occupational stress despite gender differences. In high risk and harsh workplace environment, correctional staff’ wellness and occupational stress are two interrelated issues. Nevertheless, gender differences are always appealing issues due to developmental difference between male correctional staff and female correctional staff. The difference is causing protruding quandary to female correctional staff in order to survive in the men’s world at some extent especially in the traditionally male dominated workplaces such as prison organization. The gender difference has certainly caused both genders to experience and perceive their occupational stress differently. Hence, this study seeks to examine significant differences of occupational stress level between male and female correctional staff. The study used survey method on 417 correctional staff as respondents. Research findings revealed significant difference between male and female correctional staff. The differences of roles, personality, attitude and behavior between male and female are due to biological and social influences.